Escape to Saint Lucia [videorecording (DVD)] - Spacek, Libor; Dolezalova, Petra (Galloping Films, 2024)
Saint Lucia, with its magical volcanic peaks, rain forests and rare fauna is the most romantic island in the Caribbean.